(untitled) (Jurnal Bahasa, 2015)
In Krian river (Sarawak), Malay dialect is the main lingua franca. It is spoken by the Malay community along this river and as an important interethnic interaction language in Saratok town. To date, only a few studies were carried out and no comprehensive classification is dealing with this dialect. Hence, the status of this dialect and its relationship with other Malay dialects spoken in the adjacent areas (i.e. the Saribas and Rajang Malay dialects) remain unknown. This study use three common phonological features appeared in Saribas and Rajang Malay dialects (the phonemes of /-a/, /-ɣ/ and /-l/) to examine the status of this Malay dialect. The research result found that the Krian Malay dialect is a variation of Saribas Malay by displaying the changes of /-a/ to [-ɔ], /-l/ to [-a] or [-y], and /-ɣ/ to [-ə], rather than Rajang Malay which shows the retentions of: /-a/ as [-a] and /-l/ as [-l]. Keywords: Malay dialects, Krian River, Saribas, Rajang, phonology